DEVELOPMENT OF FLY ASH-BASED GEOPOLYMER MEMBRANE FOR METHYLENE BLUE DYE REMOVAL - AHMAD DAUD, NURUL AMIRA (2021)
Fly ash-based geopolymer synthesized by reacting fly ash with an alkaline activator has a potential for membrane application due to its high mechanical strength, easy synthesis and low cost. In this research, a new fly ash-based geopolymer (FAGP) membrane was successfully synthesized and the effects of the forming agent, alkaline activator and Si/Al ratio on its membrane application were investigated. The morphology, pore structure and functional groups FAGPs were characterized using field-emission scanning electron microscopy (FESEM), Brunauer- Emmett-Teller (BET) analysis and Fourier Transform Infrared spectroscopy (FTIR) respectively. Based on the FESEM results, the membrane with 5.0 wt% egg white and 0.6 wt% of H2O2 (GE5) showed homogenous and interconnected porosity, and based on the BET result, the pore sizes of the membrane increased from 11.49 nm (GE0) to 19.60 nm (GE5). Performance analysis on methylene blue dye removal in an aqueous solution revealed that GE0-GE5 gave a significantly high removal R>90% with the highest permeation rate of 15 L/m2. h. for GE5. At the best removal condition, the final concentration of dye was recorded at 30 ppm which is below the Standard B discharge limit. Meanwhile, the mechanical properties of the modified FAGP membrane was studied through flexural strength test by varying the concentrations of sodium hydroxide (NaOH) which are 4M-12M, and Si/Al ratios at 1.86/1, 2.2/1 and 2.3/1. The optimum NaOH concentration was found to be at 10M, meanwhile Si/Al ratio of 2.3/1 resulted in a significant increase to the strength of the geopolymer membrane. Thus, geopolymer membranes derived from fly ash was proven effective for dye removal. Future works are still needed to obtain optimal FAGP to achieve targeted industrial applications.